Revision of Monstera (Araceae: Monsteroideae) of Central America - Croat, Thomas B.; Cedeño-Fonseca, Marco; Ortiz, Orlando O. (Phytotaxa, 2024)
Monstera is the taxonomically least understood genus in the Araceae family in Mesoamerica. Identification is further complicated by drastic phenotypic changes from juvenile to adult stages and the precocious flowering of some species. The reliability of traditional taxonomic characters is uncertain, as they have been primarily studied in dry herbarium specimens, with their variability in natural populations and living plants remaining largely unknown. To enhance the taxonomy of Monstera, a comprehensive revision of Central America species was conducted. This involved: (1) an exhaustive literature review; (2) examining 4500 specimens from different herbaria, including most type specimens; (3) extensive fieldwork to document plant morphology at different developmental stages through photography and herbarium preparation; and (4) circumscribing species using the gathered data. This study recognizes 52 native species in Central America. Three species are newly described here M. coclensis, M. harrisoneorum, and M. ngabensis, and one is new record for Panama. For each species, detailed morphological descriptions, habitat information, phenology, conservation status, examined specimen lists, taxonomic and nomenclatural comments, and photographs of key morphological traits are provided.